Appropriate Technology in the Treatment of Clean Water on Islamic Boarding Schools in Sungai Itik Village - Dian Rahayu Jati; Azwa Nirmala; Syaifurrahman Syaifurrahman; Muhammad Saleh; Ade Elbani (Journal of Community Based Environmental Engineering and Management, 2022)
Sungai Itik Village is located in Sungai Kakap District, Kubu Raya Regency, directly visiting Pontianak City. However, the people in Itik Village have not yet enjoyed clean water from the local water company. So that the surrounding community uses clean water sourced from rainwater or drilled wells. However, the condition of the well water is not yet suitable for use. At the As-Siddiqiyah Islamic Boarding School, it has drilled wells with a flow rate of 30 liters/minute and does not need to be sucked up with a water pump in flat, level conditions. However, the condition of the water still contains a lot of Fe2+ ions, has a metallic smell and color. This drilled well water is very possible as raw water to be processed and used as drinking water that can be consumed by the community around the Islamic boarding school. The Student Creativity Program Team of the Faculty of Engineering provides air purification solutions with the Aeration, Sedimentation and Filtration methods contributing to the local community, especially for students at Islamic Boarding Schools. The results of laboratory tests on drilled well water at the As-Siddiqiyah Islamic Boarding School show that raw water that has been treated through water treatment equipment is suitable for daily activities and does not cause health problems. The provision and management of clean water is left entirely to the students in Islamic boarding schools to maintain the continuity and maintenance of the availability of clean water.